Plummer-Vinson Syndrome: A Case Report - Muhammad Luqman; Saira Akhtar; Muhammad Adil Ramzan; Aqeela Afzal; Syed Humayun Naeem; Warda Yawar (Journal of Liaquat National Hospital)
Plummer-Vinson syndrome (PVS), also termed as sideropenic dysphagia or Paterson-Brown-Kelly syndrome, is an uncommon medical disorder characterised by three things: iron deficiency anaemia, dysphagia, and esophageal web(s), more often seen in middle-aged females. We present a case of a 45-year-old married lady who came to the medical outpatient department at Abbasi Shaheed Hospital with food swallowing difficulty, fatigue, and generalised body weakness for the past 7 months. Her hematological workup revealed microcytic hypochromic anaemia and barium studies showed smooth circumferential narrowing of the cervical esophagus at the level of the C5-C6 vertebrae (post-cricoid esophageal web). PVS was diagnosed. Endoscopic dilatation or balloon dilatation was advised to treat her dysphagia but was refused by the patient. Her iron deficiency anaemia was corrected with an intravenous iron sucrose supplementation. She was encouraged to eat an iron-rich, semi-solid diet. When she came for a follow-up after six weeks of oral iron supplementation, her condition was satisfactory, and dysphagia had improved.